Isolation and Characterization of Differentially Expressed Genes in the Mycelium and Fruit Body of Tuber borchii - Lacourt, Isabelle (American Society for Microbiology, 2002)
The transition from vegetative mycelium to fruit body in truffles requires differentiation processes which lead to edible fruit bodies (ascomata) consisting of different cell and tissue types. The identification of genes differentially expressed during these developmental processes can contribute greatly to a better understanding of truffle morphogenesis. A cDNA library was constructed from vegetative mycelium RNAs of the white truffle Tuber borchii, and 214 cDNAs were sequenced. Up to 58% of the expressed sequence tags corresponded to known genes. The majority of the identified sequences represented housekeeping proteins, i.e., proteins involved in gene or protein expression, cell wall formation, primary and secondary metabolism, and signaling pathways. We screened 171 arrayed cDNAs by using cDNA probes constructed from mRNAs of vegetative mycelium and ascomata to identify fruit body-regulated genes. Comparisons of signals from vegetative mycelium and fruit bodies bearing 15 or 70% mature spores revealed significant differences in the expression levels for up to 33% of the investigated genes. The expression levels for six highly regulated genes were confirmed by RNA blot analyses. The expression of glutamine synthetase, 5-aminolevulinic acid synthetase, isocitrate lyase, thioredoxin, glucan 1,3-β-glucosidase, and UDP-glucose:sterol glucosyl transferase was highly up-regulated, suggesting that amino acid biosynthesis, the glyoxylate cycle pathway, and cell wall synthesis are strikingly altered during morphogenesis.